Association between environmental exposure to pesticides and prevalence of asthma symptoms in rural children and adolescents living in agricultural settings in the Western Cape - Tshilengu, Eunice Muya (Department of Public Health and Family Medicine, 2025)
Background: There is conflicting evidence on the association between pesticide exposure and child asthma related outcomes in agricultural settings and limited data in developing country settings. Objectives: This study investigated the association between children's exposure to pesticides and asthma related outcomes in rural agricultural areas in Western Cape South Africa. Methods: A cross-sectional study of 700 children from three intensive agricultural areas in the rural Western Cape in June-September 2017. Guardian reported asthma outcomes and demographic information using an abbreviated version of the International Study of Asthma and Allergies in Childhood questionnaire and self-reported pesticide exposures of children was obtained. Results: The median age of children was 11 years. The prevalence of more than two reported asthma symptoms (current wheeze, wheeze attack, wheeze disturbing sleep, wheeze limiting speech and wheeze during exercise) was 8.5% across the sample. There were no statistically significant positive associations found between any of the three asthma related outcomes (including asthma symptoms score ≥ 2, parental reported asthma and current wheeze) and pesticide exposure variables. These included general pesticide exposure, farm activities, leisure activities and household pesticide exposure when adjusting for relevant confounders using multiple logistic regression analysis. Conclusion: This cross-sectional study did not find evidence of an association between self reported asthma related outcomes and pesticide exposure among rural children of the Western Cape. Longitudinal studies investigating the association using robust exposure and outcome measures are recommended.